Resgate histórico da ação e dos resusltados da extensão rural oficial do Marnhão (ACAR/EMATER-MA) - Dias, José Peregrino Araujo (2007)
The objective of this work was to rescue historically the ACAR/EMATER-MA actions and results among the years from 1964 to 1998. The referred analyses were basically in the annual reports of ACAR/EMATER-MA, among the years from 1972 to 1993. It stands out the Maranhão official rural extension particularities, such as the producers category prioritized by the technical attendance and its reasons, rural producers participation level allowed, difficulties EMATER/ACAR transformation particularly, technical personnel's training quantitative and qualitative reductions. It also approaches the consequent misunderstandings and omissions of these difficulties, that constituted the commitment reasons of the Maranhão extension action results.